Late-Onset Ornithine Transcarbamylase Deficiency and Variable Phenotypes in Vietnamese Females With OTC Mutations - Nguyen, Huy-Hoang; Khanh Nguyen, Ngoc; Dung Vu, Chi; Thu Huong Nguyen, Thi; Nguyen, Ngoc-Lan (Frontiers in Pediatrics, 2020)
Background: Ornithine transcarbamylase deficiency (OTCD) is an X- linked recessive disorder and the most common error of the urea cycle, caused by the mutations in the OTC gene. Due to X-inactivation, 15%-20% of female carriers present symptoms of OTCD at late onset, early diagnosis of OTCD by molecular analysis in females is highly desirable. The aim of the study was to identify the mutations in two unrelated Vietnamese girls suspected with OTCD and carriers in their families for definitive diagnosis and proper counselling. Case presentation: Two patients presented with an acute encephalopathy at the first admission. Biochemical tests revealed hyperammonemia, hyperlactatemia, elevated glutamine level, elevated transaminase, elevated urinary orotic and uracil acid levels, and disorder of prothrombin time. Brain magnetic resonance imaging indicated cerebral edema. Based on the clinical and laboratory results, two patients were diagnosed with urea cycle disorders. Therefore, two patients were managing to stop feeding, infuse glucose, L-carnitine, L-arginine and sodium benzoate; and hemofiltration. The two patients were alert recovered with normal blood ammonia level after 72 hours of treatment. The family history of patient 1 showed her brother died at 4 days of age due to a coma and dyspnea, while her parents were asymptomatic. Variable phenotypes were observed in three generations of the patient 2’s family, including asymptomatic (mother), affected female adults died at the first symptom (grandmother and aunt), and affected males died in the first week of life (uncle, cousin and siblings). Whole exome sequencing showed two mutations in the OTC gene, including one novel missense mutation c.365A>T in the patient 1 and one previously reported splicing mutation c.717+1G>A in the patient 2. The two mutations are evaluated as likely pathogenic and pathogenic according to the recommendations of the American College of Medical Genetics and Genomics (ACMG). Genetic analyses in the families indicated the mothers are heterozygous. Conclusion: Clinical, biochemical and molecular results accurate diagnosed these patients with late-onset OTCD. Our results explained the genetic causing and proposed the risk in the patients’ families, which could be served for genetic counseling and monitoring in prenatal diagnosis.